(untitled) (Al-Academy, 2020)
Starting from the term (forbidden montage) initiated by the French critic (Andre Bazin) as a method of processing the movies that depend on (mise en scene) achieved by the action of the camera and its ability to photograph and employ the depth of the field, in addition to the possibility of free movement without interruption in the filming environment in order to avoid montage as much as possible (the montage that distorts focus and distracts attention and moves away from realism, which is the most important theoretical pillar of Bazin in photography). The pursuit was behind a cinema that depicts its topics in one integrated snapshot with all its details thus approximating reality without any interference of montage. Our study started from this concept, which addressed processing the subjects of the achieved films without montage or clipping which divides the film, which are called the continuous one-shot films, among these films is the war film (1917) which was produced in the same year that the coronavirus pandemic sparked in 2019. Our study started to diagnose the method of processing the stories of the feature films in one continuous shot without montage, though those films were composed of a set of snapshots, yet a certain technique literally and not figuratively connected these long take shots to each other to give the impression and attract the attention to the fact that the film is composed of one continuous shot. This technique revolved around certain patterns of mechanisms and techniques that facilitated the process of composing the footage in the form of (invisible cutting) which gives the film construction the concept of (the one-shot film). The study came up with some results including determining the technique adopted in the transition which helps the feeling that the film looks as one-shot and classified the method of this technique into (deception or intrigue, cunning, concealing the transition under the mask, the quick camera movement, the visual effects of all types, and the technique of darkness and entanglement).